2022
DOI: 10.1186/s12883-021-02516-x
|View full text |Cite
|
Sign up to set email alerts
|

DL-3-n-butylphthalide promotes hippocampal neurogenesis and reduces mossy fiber sprouting in chronic temporal lobe epilepsy rats

Abstract: Background A decrease in hippocampal neurogenesis is considered an important cause of cognitive impairment, while changes in mossy fiber sprouting are closely related to development of spontaneous recurrent seizures in chronic temporal lobe epilepsy (TLE). Racemic l-3-n-butylphthalide (DL-NBP) can alleviate cognitive impairment in ischemic stroke and Alzheimer’s disease by promoting neurogenesis. DL-NBP treatment can also improve cognitive function and reduce seizure incidence in chronic epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…[18][19][20] Numerous investigations have demonstrated that NBP possesses notable neuroprotective properties in cerebral ischemia, potentially because of its capacity to diminish cerebral oedema, thus impeding oxidative stress and diminishing neuronal demise and in ammation. [21][22][23] NBP has also been documented to enhance cognitive function in Alzheimer's disease and cerebral ischemia-reperfusion injury. [24][25][26][27][28] Furthermore, prior research has indicated that NBP ameliorates cognitive function in Alzheimer's disease and cerebral ischemiareperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Numerous investigations have demonstrated that NBP possesses notable neuroprotective properties in cerebral ischemia, potentially because of its capacity to diminish cerebral oedema, thus impeding oxidative stress and diminishing neuronal demise and in ammation. [21][22][23] NBP has also been documented to enhance cognitive function in Alzheimer's disease and cerebral ischemia-reperfusion injury. [24][25][26][27][28] Furthermore, prior research has indicated that NBP ameliorates cognitive function in Alzheimer's disease and cerebral ischemiareperfusion injury.…”
Section: Discussionmentioning
confidence: 99%